Seasonal distribution and population parameters of woodland caribou in central Manitoba: implications for forestry practices - Brown, Kimberley G.; Elliott, Campbell; Messier, Francois (Rangifer, 2000)
Woodland caribou (Rangifer tarandus caribou) in the boreal forest are believed threatened by human encroachment and associated disturbances such as resource exploration and extraction. We radiocollared and monitored fifteen female woodland caribou in central Manitoba, from 1995 to 1997, to obtain information on their population range, seasonal distribution and movements in relation to forestry concerns. The population ranged over 4600 km2 within a large peatland system and concentrated their activities in two areas for both the summer and winter seasons. Females were relatively more solitary during the summer and exhibited fidelity to specific calving and summering areas averaging 83.4 km2. Individual wintering locations varied between years and among individuals. Post-rut and pre-calving mixed-sex aggregations occurred on the southern portion of the herds range. Caribou from the northern part of the range utilized a traditional travel corridor moving as far as 65 km to access the aggregation areas and their summer or winter ranges. Adult survival during the study period averaged 0.90 (95% CI, 0.80-1.00). Survival of the 1995 cohort appeared to be high as indicated by the 0.65:1 calf-cow ratio, and 30 ± 7% calf composition of observed caribou in the autumn of 1995. The annual rate of change (A,) of 1.19 (95% CI, 1.02-1.36) from January to November of 1995 indicated rhat the population was increasing at that time.